Cost-effectiveness of alternative strategies for provision of HIV preexposure prophylaxis for people who inject drugs. (13th March 2018) - Fu, Rui; Owens, Douglas K.; Brandeau, Margaret L.
Abstract : Background: Oral HIV preexposure prophylaxis (PrEP) has been recommended as a means of HIV prevention among people who inject drugs (PWIDs) but, at current prices, is unlikely to be cost-effective for all PWID. Objective: To determine the cost-effectiveness of alternative strategies for enrolling PWID in PrEP. Design: Dynamic network model that captures HIV transmission and progression among PWID in a representative US urban center. Outcome measures: HIV infections averted, discounted costs and quality-adjusted life-years (QALYs), and incremental cost-effectiveness ratios. Intervention: We assume 25% PrEP coverage and investigate four strategies: first, random PWID are enrolled (Unselected Enrollment); second, individuals are randomly selected and enrolled together with their partners (Enroll Partners); third, individuals with the highest number of sexual and needle-sharing partnerships are enrolled (Most Partners); fourth, individuals with the greatest number of infected partners are enrolled (Most Positive Partners). Results: PrEP can achieve significant health benefits: compared with the status quo of no PrEP, the strategies gain 1114 QALYs (Unselected Enrollment), 2194 QALYs (Enroll Partners), 2481 QALYs (Most Partners), and 3046 QALYs (Most Positive Partners) over 20 years in a population of approximately 8500 people. The incremental cost-effectiveness ratio of each strategy compared with the status quo (cost per QALY gained) is $272 000 (Unselected Enrollment), $158 000 (Enroll Partners), $124 000 (Most Partners), and $101 000 (Most Positive Partners). All strategies except Unselected Enrollment are cost-effective according to WHO criteria. Conclusion: Selection of high-risk PWID for PrEP can improve the cost-effectiveness of PrEP for PWID. Abstract : Supplemental Digital Content is available in the text